2017
DOI: 10.3389/fphys.2017.01060
|View full text |Cite
|
Sign up to set email alerts
|

Connexins in the Central Nervous System: Physiological Traits and Neuroprotective Targets

Abstract: Cell-to-cell interaction and cell-to-extracellular environment communication are emerging as new therapeutic targets in neurodegenerative disorders. Dynamic expression of connexins leads to distinctive hemichannels and gap junctions, characterized by cell-specific conduction, exchange of stimuli or metabolites, and particular channel functions. Herein, we briefly reviewed classical physiological traits and functions of connexins, hemichannels, and gap junctions, in order to discuss the controversial role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 99 publications
0
41
0
Order By: Relevance
“…In recent years, studies have indicated that Cx43-containing GJCs and Hcs are the main cell adhesion channels in astrocytes and maintain the homeostasis of the neural microenvironment in the CNS [10]. However, abnormal opening of Cx43Hcs on the surface of reactive astrocytes can release small molecules into the intercellular space under pathological conditions [33].These small molecules in uence the steady state of the cell microenvironment, which induces in ammatory and cell death programs by regulating the crosstalk between reactive astrocytes and other cells in the CNS [34]. De nite evidence has shown that like Cx43 overexpression, abnormal Cx43Hc opening leads to further brain damage in different CNS diseases.Suppressing pathological Cx43 expression can reduce the formation of hemichannels and promote the production of survival genes [35,36].Inhibition of Cx43Hcs with selective blockers has been shown to provide protective effects under different pathological stresses [37].Our previous research con rmed that Cx43Hc blockers signi cantly alleviate neurological de cits and infarct volume in a rodent model of ischemic stroke [12,38].To our knowledge,there have been no reports on the characteristics of Cx43Hcs after ICH injury.In our current study, sustained overexpression of Cx43 coupled with abnormal opening of Cx43Hcs was observed in a mouse model of ICH injury (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have indicated that Cx43-containing GJCs and Hcs are the main cell adhesion channels in astrocytes and maintain the homeostasis of the neural microenvironment in the CNS [10]. However, abnormal opening of Cx43Hcs on the surface of reactive astrocytes can release small molecules into the intercellular space under pathological conditions [33].These small molecules in uence the steady state of the cell microenvironment, which induces in ammatory and cell death programs by regulating the crosstalk between reactive astrocytes and other cells in the CNS [34]. De nite evidence has shown that like Cx43 overexpression, abnormal Cx43Hc opening leads to further brain damage in different CNS diseases.Suppressing pathological Cx43 expression can reduce the formation of hemichannels and promote the production of survival genes [35,36].Inhibition of Cx43Hcs with selective blockers has been shown to provide protective effects under different pathological stresses [37].Our previous research con rmed that Cx43Hc blockers signi cantly alleviate neurological de cits and infarct volume in a rodent model of ischemic stroke [12,38].To our knowledge,there have been no reports on the characteristics of Cx43Hcs after ICH injury.In our current study, sustained overexpression of Cx43 coupled with abnormal opening of Cx43Hcs was observed in a mouse model of ICH injury (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the specific permeability properties and features of Cxs depend on the functionality of the distinct channels that they form. This specificity regulates channel conductance, electrical communication and metabolic coupling between cells (Vicario, 2017).…”
Section: Properties Of Connexin Channelsmentioning
confidence: 99%
“…Additionally, pharmacological blockade of Cx43 with both GJ or HC blockers offers neuroprotection to motor neurons cultured with hSOD G93A astrocytes, suggesting a detrimental role of Cx43 in ALS neurodegenerative models (Almad, 2016). Blocking Cx43 has also shown protective effects in other neurodegenerative conditions, such as hypoxia and glaucoma (Vicario, 2017). Moreover, strategies combining Cx mimetic peptides to target glial and endothelial GJs and HCs with drugs that preclude electrical synaptic signaling pathways have been considered to improve survival of neurons in neurodegenerative diseases and injuries.…”
Section: Astrocytes and Connexins During Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the brain, several different connexin subtypes are expressed, with preference shown to specific isoforms in different cell lineages. For example, neurons are canonically associated with connexins 36 and 50 (although connexin 32 has been described in neurons), oligodendrocytes favour connexins 29, 32 and 47 while microglia mainly express connexins 32, 36 and 43 189,190 . In Paper II, we investigated the possibility that oligomeric α-syn could be taken up by neurons and oligodendrocytes in a manner mediated by connexin 32.…”
Section: Gap Junction Proteinsmentioning
confidence: 99%